2006
DOI: 10.1097/00006982-200602000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Viral and Immune Pathogenesis of Immune Recovery Uveitis in Patients With Healed Cytomegalovirus Retinitis

Abstract: Inflammatory IRU can be differentiated from active CMV retinitis by the presence of IL-12, less IL-6, and absence of detectable CMV replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 13 publications
1
45
0
1
Order By: Relevance
“…Over a longer time span, some patients also experience immune recovery uveitis (IRU), presenting as ocular inflammation (vitritis, macular edema, or formation of epiretinal membranes) and decreased vision. Most IRU patients also have a history of treated CMV retinitis before ART (126). Studies of patients who began ART in Western Australia before 1998 associated CMV retinitis and/or encephalomyelitis experienced during immune recovery on ART (CMV/encephalitis IRD) with a common major histocompatibility complex haplotype (HLA-A2, B44, TNFA-308*2, DR4) (114), suggesting similar immunopathological mechanisms.…”
Section: Ird Manifested As CMV Retinitis or Viral Encephalomyelitis: mentioning
confidence: 99%
See 1 more Smart Citation
“…Over a longer time span, some patients also experience immune recovery uveitis (IRU), presenting as ocular inflammation (vitritis, macular edema, or formation of epiretinal membranes) and decreased vision. Most IRU patients also have a history of treated CMV retinitis before ART (126). Studies of patients who began ART in Western Australia before 1998 associated CMV retinitis and/or encephalomyelitis experienced during immune recovery on ART (CMV/encephalitis IRD) with a common major histocompatibility complex haplotype (HLA-A2, B44, TNFA-308*2, DR4) (114), suggesting similar immunopathological mechanisms.…”
Section: Ird Manifested As CMV Retinitis or Viral Encephalomyelitis: mentioning
confidence: 99%
“…Two studies demonstrated T-cell activity without active CMV replication in IRU. Schrier et al (126) compared fluids from eyes with IRU and those with CMV retinitis (collected pre-ART and CMV DNA positive). TNF, IL-4, and several chemokines were undetectable, but samples from eyes with IRU contained less IL-6 and more IL-12 than those from eyes with CMV retinitis.…”
Section: Ird Manifested As CMV Retinitis or Viral Encephalomyelitis: mentioning
confidence: 99%
“…Immune recovery uveitis was diagnosed as the presence of intraocular inflammation in a patient with healed CMV retinitis who had an immune response to HAART and was characterized by vitritis, macular edema, or epiretinal membrane formation in association with specific cytokine profiles (18) .…”
Section: Methodsmentioning
confidence: 99%
“…IRU je povezan z zmernim poslabšanjem vidne ostrine, niso pa dokazali njegove povezave z aktivno replikacijo CMV ali z nadaljevanjem oz. prenehanjem anti--CMV-zdravljenja (42,43). Zdravljenje HAART lahko zažene CMV retinitis pri bolniku brez predhodne okužbe s CMV (angl.…”
Section: Oportunistične Okužbe Mrežnice In žIlnice 2421 Citomegalounclassified